Network Dyads in Entrepreneurial Settings: A Study of the Governance of Exchange Relationships - Larson, Andrea (Administrative Science Quarterly, 1992)
Investigates network dyads and the manner in which control is exercised in these structures. Four entrepreneurial, high growth firms, each from a different industry, were selected to participate in this ethnographic analysis. The represented industries are telephone equipment, clothing, computer hardware, and environmental support systems. Seven network dyads were identified for the four firms considered. The partnerships were typically other members of the value chain - e.g., suppliers, distributors and final customers. The analysis identified three phases for the network dyad development: preconditions for exchange, conditions to build, and integration and control. The first phase, preconditions, utilized prior relations in addition to personal and firm reputations to reduce uncertainty and establish expectations and obligation. The second phase, the building process, has significant reliance on the trust and the development of reciprocity norms. The third phase is marked by three forms of integration: operational, strategic, and social control. Examination of the four firms and their seven dyadic relationships support the model. These firms were found to be engaged in stable, sustained relationships with a high degree of cooperation and collaboration. The mode of exchange found in these dyadic relationships is characterized as a network form of governance, which appears to be beneficial to high growth firms. Further research using this model could be done for R&D partnerships, cooperative marketing agreements, and other forms of strategic alliances and joint ventures. (SRD)